Benzothiazole-quinoline based probe for simultaneous colorimetric detection of CN- and Cu2+ ions, with fluorescence sensing for Cu2+: Mechanistic insights and practical applications in environmental monitoring and cellular analysis - P.S. Umabharathi; S. Karpagam; Tiasha Dasgupta; Ramasamy Tamizhselvi (Heliyon)
The development and synthesis of notably targeted and colorimetric sensor based on an azomethine compound for the distinct recognition of Cu2+ and CN− ion individually in an aqueous dimethyl formamide solution is performed. In the presence of CN− and Cu2+, the sensor BTZ showed impressive colorimetric changes, going from pale yellow to orange and pale yellow to dark yellow, respectively. In the meantime, FL spectrum (Cu2+) and UV–vis spectroscopy (CN−/Cu2+) were used to assess the sensing features. The plausible binding mechanisms of CN− and Cu2+ ions with sensor BTZ have been studied using the 1H NMR titration, Job's plot and DFT technique. The bathochromic shift produced by the intramolecular charge transfer (ICT) transition may have been the source of the phenomenon. Furthermore, CN− ion in the commercial substance is quickly identified and measured with the naked eye by using sensor BTZ. It was found that the BTZ's LOD for CN− and Cu2+ was 0.280 × 10−7 M and 1.153 × 10−7 M, respectively. Moreover, 1:1 binding ratio for the reaction of CN− and Cu2+ ions with sensor BTZ were demonstrated by Job's plot, which was dependent on analytical data. The findings show that BTZ is an easy-to-use and practical probe for concurrently sensing cyanide and copper ions in environmental samples and living cells that have less cytotoxicity.